Governance of Street Lighting Provision in System Context, Driver, and Collaboration Dynamics Dimensions (Journal of Namibian Studies : History Politics Culture, 2023)
Energy efficiency is currently a very popular topic because the world's need for energy continues to increase every year. Street lighting is one sector that has great potential to be targeted for energy efficiency. The use of energy-saving street lighting technology is not easy to realize, due to limited technical knowledge, namely, the components of street lighting do not meet the Indonesian National Standard. Meanwhile, non-technical problems are limited budgets in providing street lighting. If the procurement of street lighting is associated with government budget constraints, then it is not wrong for the provision to be handed over to businesses or private entities. In this study, researchers analyzed the process of collaborative governance and the Public-Private Partnership scheme in providing street lighting in the city of Bandung. This study uses a qualitative approach. Determination of the sample by using critical sampling. Data collection techniques by performing observation, interview, documentation tracing, and audiovisual while the operational design in this study uses an integrative framework for a collaborative governance approach, namely system contexts, drivers, and collaboratives dynamics.